Hornet flight - Follett, Ken
It is June 1941 and the war is not going well for England. Somehow, the Germans are anticipating the RAFUs flight paths, and shooting down British bombers with impunity. Filled with knife-edge suspense and rich, tantalizing characters, this is Ken Follett writing at the top of his form -- unforgettable storytelling from an unforgettable writer